Pengaruh Leverage dan Capital Intensity pada Tax Avoidance dengan Proporsi Komisaris Independen sebagai Variabel Pemoderasi - Sinaga, Cyntia Habibah; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p01, 2019)
This study aims to obtain empirical evidence of the effect of leverage and capital intensity on tax avoidance with the proportion of independent commissioners as moderating variable. The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The method of determining the sample used was purposive sampling and obtained 200 observations. Data analysis techniques using multiple linear regression analysis and Moderated Regression Analysis (MRA). The results of the analysis show that leverage has a positive effect on tax avoidance. This means that the more debt the company uses to finance assets, the higher level of tax avoidance. Capital intensity has a negative effect on tax avoidance. This means that the more capital invested by the company in the form of fixed assets, the lower level of tax avoidance. The proportion of independent commissioners does not moderate the effect of leverage and capital intensity on tax avoidance. Keywords : Leverage, capital intensity, independent commissioners, tax avoidance